Tradução de histórias em quadrinhos japonesas: análise do mangá "Cavaleiros do Zodíaco" no Brasil - Freire, Francisco Allan Montenegro (2020)
The theme of this work is the analysis of translation of Japanese comics, the manga. Based on the translated and retranslated Portuguese versions of Masami Kurumada's work, “Cavaleiros do Zodíaco” (Saint Seiya), an exploratory research of the bibliographic type was performed. it was delimited as corpus the first volume of the most recent version of “Saint Seiya Cavaleiros do Zodíaco - Kanzenban” (Kurumada, 2016), published by Japan Brazil Communication (JBC) and its correspondents in the preceding editions, namely the volumes 1 and 2 in the previous version also produced by JBC from 2012, and volumes 1, 2 and 3 of the two editions published in 2000 and 2004 by the publisher Conrad. From this analysis of the translation of this manga, it was intended to expand the field of research on manga in Translation Studies by addressing the obstacles of translation in this type of publication. The study of the four different Brazilian editions of "Cavaleiros do Zodíaco" made it possible to point out differences in macrostructure, the approach to paratext and the aspect of back-translation; the context that led to the production of different Portuguese versions of this same manga was investigated, as well as pointing out a possible profile of the manga translator, in addition to delving into the main translation obstacles pointed out by authors such as Oka (2005) and Fonseca (2011 ), also addressing the perspective of the theory of analysis of the deforming forces system elaborated by Berman (2013).